1971
DOI: 10.1073/pnas.68.12.2913
|View full text |Cite
|
Sign up to set email alerts
|

Specific cleavage of simian virus 40 DNA by restriction endonuclease of Hemophilus influenzae

Abstract: A bacterial restriction endonuclease has been used to produce specific fragments of SV40 DNA. Digestion of DNA from plaque-purified stocks of SV40 with the restriction endonuclease from Hemophilus influenzae gave 11 fragments resolvable by polyacrylamide gel electrophoresis, eight of which were equimolar with the original DNA. The fragments ranged from about 6.5 X 106 to 7.4 X 104 daltons, as determined by electron microscopy, DNA content, or electrophoretic mobility.The small oncogenic virus, SV40, contains d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
156
0
1

Year Published

1972
1972
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(157 citation statements)
references
References 19 publications
0
156
0
1
Order By: Relevance
“…On the other hand, this value is in disagreement with the estimate of Griffith [17], who has reported that an SV4O minichromosome is formed of 21 nucleosomes, each containing 170 base pairs, connected by bridges of about 40 base pairs. It is likely that due to some electron microscopic artifact the measurements of Grifjith have led to an underestimation, since 21 nucleosomes, each containing 170 base pairs, connected by 40 base pair bridges, cannot account for the total SV40 genome which contains about 5000 base pairs [21,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this value is in disagreement with the estimate of Griffith [17], who has reported that an SV4O minichromosome is formed of 21 nucleosomes, each containing 170 base pairs, connected by bridges of about 40 base pairs. It is likely that due to some electron microscopic artifact the measurements of Grifjith have led to an underestimation, since 21 nucleosomes, each containing 170 base pairs, connected by 40 base pair bridges, cannot account for the total SV40 genome which contains about 5000 base pairs [21,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The spreading conditions used were 50% formamide, 0.1 M buffer solution (Keegstra et al, 1977) for the specimens used for mapping and 30% formamide 0.1 M buffer solution for the annealing control experiments. $1X174 replicative form DNA with at least one nick in one of the strands (RFII) was used as an internal length reference (Lang et al, 1967;Brown and Vinograd, 1974;Danna and Nathans, 1971;Stiiber and Bujard, 1977). The specimens were examined and photographed in a Philips EM 301 at a (film) magnification of 26000 x on Kodalith LR film.…”
Section: Methodsmentioning
confidence: 99%
“…In 1970, Hamilton Smith and his colleagues at Johns Hopkins University reported that a restriction enzyme they named HindII-a protein isolated from the bacterial pathogen, Haemophilus influenzae-recognizes particular nucleotide sequences in DNA and cuts duplex DNA site-specifically at these sequences (36). The following year, Karen Danna and Daniel Nathans found that the HindII endonuclease cleaves DNA of the mammalian tumor virus SV40 into 11 fragments that can be separated by acrylamide gel electrophoresis, demonstrating the utility of restriction endonucleases for DNA analysis (37). Arber, Nathans, and Smith received the 1978 Nobel Prize in Physiology or Medicine for these accomplishments.…”
Section: Restriction Endonucleasesmentioning
confidence: 99%